Persistent barriers to care; a qualitative study to understand women's experiences in areas served by the midwives service scheme in Nigeria. Issue 1 (December 2016) - Exley, Josephine; Pitchforth, Emma; Okeke, Edward; Glick, Peter; Abubakar, Isa; Chari, Amalavoyal; Bashir, Usman; Gu, Kun; Onwujekwe, Obinna
Abstract Background The Nigerian Midwives Service Scheme (MSS) is an ambitious human resources project created in 2009 to address supply side barriers to accessing care. Key features include the recruitment and deployment of newly qualified, unemployed and retired midwives to rural primary healthcare centres (PHCs) to ensure improved access to skilled care. This study aimed to understand, from multiple perspectives, the views and experiences of childbearing women living in areas where it has been implemented. Methods A qualitative study was undertaken as part of an impact evaluation of the MSS in three states from three geo-political regions of Nigeria. Semi-structured interviews were conducted around nine MSS PHCs with women who had given birth in the past six months, midwives working in the PHCs and policy makers. Focus group discussions were held with wider community members. Coding and analysis of the data was performed in NVivo10 based on the constant comparative approach. Results The majority of participants reported that there had been positive improvements in maternity care as a result of an increasing number of midwives. However, despite improvements in the perceived quality of care and an apparent willingness to give birth in a PHC, more women gave birth at home than intended. There were some notable differences between states, with a majority of women in one northern state favouring home birth, which midwives and community members commented stemmed from low levels of awareness. The principle reason cited by women for home birth was the sudden onset of labour. Financial barriers, the lack of essential drugs and equipment, lack of transportation and the absence of staff, particularly at night, were also identified as barriers to accessing care. Conclusions Our research highlights a number of barriers to accessing care exist, which are likely to have limited the potential for the MSS to have an impact. It suggests that in addition to scaling up the workforce through the MSS, efforts are also needed to address the determinants of care seeking. For the MSS this means that the while the supply side, through the provision of skilled attendance, still needs to be strengthened, this should not be in isolation of addressing demand-side factors.